Empirical strategies to eliminate life-cycle bias in the intergenerational elasticity of earnings literature - Jan Leonard Stuhler (Institute for the Study of Labor (IZA), 2010)
I argue that the empirical strategies for estimation of the intergenerational elasticity of lifetime earnings that are currently employed in the literature might not eliminate bias arising from lifecycle effects. Specifically, I demonstrate that procedures based on the generalized errors-invariables model suggested by Haider and Solon (2006) or the consideration of differential earnings growth rates across subpopulations may not yield unbiased or consistent estimates. I further argue that instrumental variable estimators will not identify an upper bound for the true population parameter.
Keywords: J62; C23; 330; intergenerational mobility; intergenerational elasticity of earnings; life-cycle bias; generalized errors-in-variables model